Structural phasic characteristics of nanoparticles oxides Samarium-153 by influence gamma activation - Dikiy, N.P.; Krasnoselskiy, N.V.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V. (Problems of Atomic Science and Technology, 2023)
The isotope ¹⁵³Sm (T₁/₂ = 46.3 h, E = 810 keV) which emit is both therapeutic beta and diagnostic gamma energies and it is ideal for therapy plus diagnostic application. The specific activity of ¹⁵³Sm was increased by using the Szilard-Chalmers reaction and nanoparticles Sm₂O₃ after gamma activation on LAE. It is shown that the isotope ¹⁵³Sm after gamma activation there are no radioactive impurities and no changes of chemical and phasic structure. Ізотоп ¹⁵³Sm (T₁/₂ = 46.3 год, E = 810 кеВ) являється ідеальним емітером для проведення бета-терапії та гамма-діагностики. Питома активність ¹⁵³Sm була підвищена завдяки використанню реакції Сціларда-Чалмерса та наночастинок Sm₂O₃ після гамма-активації на лінійному прискорювачі електронів. Показано, що ізотоп ¹⁵³Sm після гамма-активації не містить радіонуклідних домішок та не втрачає хімічну та фазову структури.